Case report: histopathology and molecular pathology analysis on enteric tissue of a COVID-19 patient - Yanling Feng; Dong Zeng; Lvyin Hu; Yuexiang Yang; Shu Song; Yuhan Shi; Jingjing Xu; Wenjuan Guo; Yun Ling; Tangkai Qi; Qingguo Wu; Feng Li; et al. (BMC, 2021)
Abstract Aims Patients with COVID-19 can also have enteric symptoms. Here we analyzed the histopathology of intestinal detachment tissue from a patient with COVID-19. Methods The enteric tissue was examined by hematoxylin & eosin stain, PAS (Periodic acid-Schiff) staining, Gram staining, Ziehl-Neelsen stain and Grocott's Methenamine Silver (GMS) Stain. The distribution of CD3, CD4, CK20 and CD68, cytomegalovirus (CMV) and Herpes Simplex Virus (HSV) antigen were determined by immunohistochemistry. In situ hybridization (ISH) of SARS-CoV-2 and Epstein-Barr virus-encoded small RNA (EBER) were also performed. Results We observed mucosal epithelium shedding, intestinal mucosal erosion, focal inflammatory necrosis with hemorrhage, massive neutrophil infiltration, macrophage proliferation accompanied by minor lymphocyte infiltration. Fungal spores and gram positive cocci but not mycobacteria tuberculosis were identified. Immunohistochemistry staining showed abundant CD68+ macrophages but few lymphocytes infiltration. HSV, CMV and EBV were negative. ISH of SARS-CoV-2 RNA showed positive signal which mostly overlapped with CD68 positivity. Conclusions The in situ detection of SARS-CoV-2 RNA in intestinal macrophages implicates a possible route for gastrointestinal infection. Further study is needed to further characterize the susceptibility of enteric cells to SARS-CoV-2 infection.